Confidentiality and family involvement in healthcare: a mixed-method approach of physicians’ perspectives in Jordan - Reema Karasneh; Sayer Al-Azzam; Mohammad Nusair; Abdel-Hameed Al-Mistarehi; Mamoon A. Aldeyab; Islam Massad (BMC Medical Ethics)
Abstract Background With the evolving person-centered care approach, the importance of family involvement is increasingly recognized to promote comprehensive treatment. However, determining when and how to disclose patient information to families without compromising privacy rights while ensuring optimal patient care poses an ethical challenge. Therefore, we aimed to explore physicians’ attitudes regarding sharing patient data with family members and protecting patient information. Methods A convergent (i.e., concurrent) mixed-methods approach was employed, integrating quantitative data collected through a questionnaire distributed to physicians and qualitative data were obtained through semi-structured interviews. Results Data from 221 physicians in Jordan revealed that only 48% would consistently seek patient consent before data disclosure, with the majority agreeing that they would share patient information with families under circumstances where family assistance is crucial (n = 180, 81.4%) or when the patient is unable to understand the information (n = 181, 81.9%). This was justified by the active involvement of family members in the treatment process (n = 182, 81.4%). Qualitative data from 14 physicians were obtained, and their perspectives revealed two main themes: 1) “Attitudes Toward Data Sharing with Patients’ Families,” which encompassed “inability of patients to make decisions,” “family involvement due to concerns,” and “pressure from family members and 2) “Significance of Patient Confidentiality “ which included “building patient trust” and “preventing harm to patients.” Conclusion A balanced approach that addresses complexities in patient data disclosure and family involvement in healthcare is necessary for fostering trust, supporting informed decision making and facilitating better health outcomes.